Research on the minimum network loss optimization control strategy of the active distribution network based on the distributed power flow controller - Liu, Zhu; Wang, Jinfeng; Guo, Guowei; Feng, KangHeng; Zhan, Ximei; Peng, Fadong; Gong, Dehuang; Tang, Aihong; Lulu, Ma; Xiang, Caili (Frontiers in Energy Research, 2024)
With large-scale access to distributed new energy, the power flow form of the distribution network tends to be complex. The distribution loop network rate increases, resulting in serious circulation of the distribution network, which causes great pressure on the loss of the distribution network. The problem of network loss change caused by distributed new energy grid connection, coupled with the inconsistency between load fluctuation and output power change of distributed new energy, will have a significant impact on the safety, reliability, and economic operation of the distribution network. Therefore, it is urgent to have good economic and technical means of power flow control. In this paper, a minimum network loss optimization control strategy for active distribution networks based on a distributed power flow controller is proposed. Firstly, according to the characteristics of the distribution network load and the new energy power supply along the distribution line, the multiple sub-modules of the distributed power flow controller are arranged in sections in the distribution loop network line. The regulation effect of the distributed power flow controller on the voltage and power flow of the distribution loop network is analyzed. The loop network current equation and power loss equation after the distributed power flow controller are constructed respectively, and the power equation with the minimum active loss of the active distribution loop network is derived. Secondly, the control strategy of minimum network loss of active distribution network based on distributed power flow controller is proposed. Finally, the simulation model of the active distribution loop network is constructed by PSCAD / EMTDC. The loss of the loop network before and after the distributed power flow controller is simulated and analyzed, and the effectiveness of the proposed strategy is verified.